Antropologiczne podstawy logoterapii Viktora E. Frankla - Karol Michalski (Studia Philosophiae Christianae, 2023)
The specific mode of being of the human being is characterized by the coincidence of three different types of being. Hence, the human being is physical (corporeal), psychic and noetic (spiritual) at the same time. All three dimensions of human existence are interwoven and have a special relationship to each other. While the physical and psychological dimensions are closely related, man can rise above his psychophysics by virtue of his spiritual dimension. With logotherapy, Viktor E. Frankl devised an approach that aims in a special way at establishing a prominent position for the spiritual dimension. The spiritual dimension enables people to distance themselves from themselves (self-distancing) and creates the possibility to step out of themselves (self-transcendence) and concentrate on things in the outside world. Through these two possibilities, man can make his life meaningful in the world and get rid of pathological symptoms of mental disorders. The article shows the anthropological basis of Frankl’s logotherapy, emphasizing the aspect of human freedom.